Attitudes of Generation Z towards coffee consumption in Vietnam - Nguyen, Thi Ngoc Ha; Stříteský, Václav; Kottika, Efthymia, 1982-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis aimed to explore the core attitudes and perceptions of Generation Z towards coffee consumption in Vietnam. In this paper, qualitative approaches were used to interpret the data from in-depth interviews with young Vietnamese consumers. The study revealed that Generation Z in Vietnam considers coffee drinking as a youth culture, which is trendy and globalized. Drinking coffee can be seen as an integral part of their life. The main reason for drinking coffee is to socialize. Stimulating effects of coffee such as staying awake and energy boosts are also key drivers. Gen Z mostly drinks coffee on a daily basis with a significant preference for Vietnamese iced coffee with condensed milk. However, they are also experimental and open to trying new flavors and coffee places. The study showed some differences in coffee preferences by gender. The most important factor affecting Gen Z’s coffee consumption is taste and aroma, followed by price, ambiance, and convenience. As digital natives, social media strongly influences Gen Z’s coffee drinking choices and patterns. Surprisingly, Vietnamese Gen Z does not consider drinking coffee for its health benefits, and at the same time, the health concerns related to coffee consumption are not at the forefront of lifestyle choices unless symptoms or adverse effects are directly experienced. Young people in Vietnam do not prioritize sustainability in their choices, yet there are some potential changes in the future. The findings can contribute to the literature related to this industry and may serve as a reference for future research in this area. Recommendations for coffee businesses are made in the end to better target and serve Gen Z customers, potentially leading to increased revenue and customer satisfaction.
Vedoucí práce: Václav Stříteský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses